Urgensi pembatasan periode jabatan presiden: Menjamin stabilitas demokrasi dan akuntabilitas kekuasaan - Baihaki, Moch. Ivan (Maliki Interdisciplinary Journal, 2025)
The limitation of presidential terms is a fundamental principle in maintaining democratic stability and enhancing accountability of governance. This policy plays a vital role in preventing excessive power concentration, fostering leadership regeneration, and reducing the risk of authoritarianism. This study aims to explore the urgency of limiting presidential terms by analyzing its impact on political stability, preventing authoritarian tendencies, and sustaining democracy. A literature review was conducted to examine cases from various countries that have either implemented or not implemented term limits for presidents. The findings highlight that presidential term limits contribute significantly to strengthening democratic systems by enabling political regeneration and preventing power domination. However, the implementation of this policy often encounters challenges, such as resistance from political elites and insufficient democratic cultures in certain contexts. Thus, comprehensive and integrated policy strategies are essential to ensure that presidential term limits are effectively and consistently enforced within a sustainable democratic framework.